PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PRODUKSI DAN PERDAGANGAN KOSMETIK ILEGAL DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Ujang Solihin; Efa Laela Fakhriah (Iustitia Omnibus (Jurnal Ilmu Hukum), 2021)
ABSTRACT Technological developments make it easier for business actors to sell cosmetic products by way of buying and selling both directly and online. But how many were abused cosmetic sales by business actors to sell products without a distribution permit as mentioned in Law Number 36 of 2009 cocerning Health and Regulation of the Minister of Health Number 1190 of 2010 about medical device distribution permit. Sanctions for those who violate these provisions, that Manufacturers or sellers of cosmetics that do not meet safety standards, efficacy and quality can be jailed for 10 (ten) years and fined (1) 1 (one) billion rupiah as mentioned in Article 196 Law Number 36 of 2009 concerning Health. Meanwhile, cosmetics manufacturers or sellers who does not has distribution permit can be imprisoned for 15 (fifteen) years and fined 1.5 billion rupiah as mentioned in Article 197 Law of Health. Identification of the problem, such as: (1) how far the law enforcement on application Law Number 36 of 2009 concerning Health Against Perpetrators of Criminal Acts of Illegal Cosmetic Product Trading? and (2) what are the implementation barriers on Law Number 36 of 2009 concerning Health against Perpetrators of Criminal Acts of Illegal Cosmetic Product Trading? The approach method in this research is normative juridical and empirical juridical, with descriptive analytical research specifications. Data obtained through secondary data primary, secondary and tertiary legal materials. Data collection techniques that will be carried out in this research are document studies and interviews. Data analysis used qualitative juridical methods. The results of this thesis such as: (1) Law enforcement on application Law Number 36 of 2009 concerning health Against Perpetrators of Criminal Acts of Illegal Cosmetic Product Trading has not been effective because there are still traders who sells cosmetics without having a distribution permit as stipulated in the regulations. (2) There are internal and external obstacles in monitoring the circulation of illegal cosmetics by BPOM. It is hoped that the BPOM and the police, in order to further enhance cooperation in efforts to overcome the circulation of counterfeit cosmetics, from monitoring incoming counterfeit goods to the missuse of industrial goods mixed into fake cosmetics, are expected to face the obstacles that arise then BPOM adds the number of human resources, provides counseling to the community, increases the budget in order to achieve good and equitable counseling. Key Words: Cosmetics. Enforcement, Illegal, Law, Product, Trading.